Synthesis of New Zerumbone Hydrazones and Their In-vitro Anticancer Activity - Vu, Vu V.; Vu, Tran K. (Current Bioactive Compounds, 2021)
Background: A series of new zerumbone hydrazones 5a-f and 9a-f have been synthesized in via an in situ procedure in high yields. The structure of synthesized compounds has been confirmed using 1H, 13C NMR and HR-MS. The bioassay result showed that several compounds exhibited cytotoxic effects against three human cancer cell lines, including HepG-2, SK-LU-1, and MCF-7. Compound 9a showed the best cytotoxic effect against HepG-2, SK-LU-1, and MCF-7 with IC50 values of 8.20, 6.66, and 9.35 μM, respectively. Objective: This study aims at developing new zerumbone hydrazones as anticancer agents based on zerumbone, a natural compound wildly growing in Vietnam. Methods: A series of new zerumbone hydrazones was designed, synthesized, and evaluated for cytotoxicity against three human cancer cell lines, including HepG-2, MCF-7, and SKLu-1, using the MTT method. Results: The bioassay result showed that several compounds exhibited cytotoxic effects against three human cancer cell lines, including HepG-2, SK-LU-1, and MCF-7. Especially, compound 9a displayed the best cytotoxic effect against HepG-2, SK-LU-1, and MCF-7 with IC50 values of 8.20, 6.66, and 9.35 μM, respectively. Conclusion: The research results suggest that some compounds could be considered as leads for the future design of zerumbone hydrazones in which bio-isosteric replacements in theortho position of the phenyl ring could be performed to improve the cytotoxic activity.
Keywords: synthesis